Cognitive Joyce (Cognitive Studies in Literature and Performance, 2018)
This collection is the first book-length study to re-evaluate all of James Joyce's major fictional works through the lens of cognitive studies. Cognitive Joyce presents Joyce's relationship to the scientific knowledge and practices of his time and examines his texts in light of contemporary developments in cognitive and neuro-sciences. The chapters pursue a threefold investigation-into the author's "extended mind" at work, into his characters' complex and at times pathological perceptive and mental processes, and into the elaborate responses the work elicits as we perform the act of reading. This volume not only offers comprehensive overviews of the oeuvre, but also detailed close-readings that unveil the linguistic focus of Joyce's drama of cognition. .